2015
DOI: 10.12659/msm.895255
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible Reconstituted High-Density Lipoprotein Nano-System as a Probe for Lung Cancer Detection

Abstract: BackgroundEarly detection of cancer is critical and is expected to contribute significantly to the success of cancer therapy and improvement of patient survival rates.Material/MethodsA biocompatible, reconstituted, high-density lipoprotein (rHDL)-based nano-system containing calcium carbonate and near-infrared fluorescence dye (NIRF), methylene blue (MB), was fabricated and characterized by particle size, zeta potential, and morphology observation. The safety profile was confirmed by bovine serum albumin (BSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Due to its ability to target specific cell types, HDL particles have been used extensively in drug delivery. Reconstituted HDL nanoparticles containing fluorescent calcium carbonate were able to serve as a probe for lung cancer detection in vivo . Their targeting mechanism relied on targeting scavenger receptor class B member I (SR‐BI), which is highly expressed on some cancerous cells and has an affinity to HDL .…”
Section: Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its ability to target specific cell types, HDL particles have been used extensively in drug delivery. Reconstituted HDL nanoparticles containing fluorescent calcium carbonate were able to serve as a probe for lung cancer detection in vivo . Their targeting mechanism relied on targeting scavenger receptor class B member I (SR‐BI), which is highly expressed on some cancerous cells and has an affinity to HDL .…”
Section: Proteinsmentioning
confidence: 99%
“…Reconstituted HDL nanoparticles containing fluorescent calcium carbonate were able to serve as a probe for lung cancer detection in vivo . Their targeting mechanism relied on targeting scavenger receptor class B member I (SR‐BI), which is highly expressed on some cancerous cells and has an affinity to HDL . In another example, lymphoma cells that express SR‐BI were also targeted effectively in vivo with synthetic, gold‐templated HDL nanoparticles .…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments found that in the SR-BI knockout mouse model, the tumor area as well as in vitro cell proliferation and migration decreased. Lu et al [11] constructed recombinant HDL (rHDL)/MB/CCPs on the basis of rHDL to develop a safe tumor-targeting probe for tumor detection. SR-BI is highly expressed in multiple tumor cell lines, including prostate, breast, liver, rectal, pancreatic, ovarian, and nasopharyngeal cells.…”
Section: Sr-bi and Malignant Tumorsmentioning
confidence: 99%
“…Petri and Kratzer revealed that apoA-I could bind with SR-BI specifically expressed on brain microvascular endothelial cells and astrocytes, which contributes to transferring HDL into brain to mediate intracerebral lipid metabolism in the form of transcellular transport of endothelial cells and uptake of astrocytes (Kratzer et al, 2007;Petri et al, 2007). Besides, it has also been reported that the liposomes decorated with apoA-I could be uptaken by rat glioma cells (C6 cells) via SR-BI which is also abundant on the surface of cancer cells (Hong et al, 2007;Park et al, 2010;Lu et al, 2015;Rajora and Zheng, 2016). Relating to or produced by the mediated effect of apoA-I as above, rHDL might be endowed with the excellent capacity of transporting across BBB, accumulating in the brain and tumor.…”
Section: Introductionmentioning
confidence: 99%